Revisiting linkability for vehicular communications: Continuous linkability - Axon, L (2015)
Vehicular communications have important applications for improving the safety of our increasingly populated roads, however they have privacy implications: the broadcast of safety messages can create opportunities for tracking of vehicles and drivers. For several proposed safety applications, it is desirable that nearby vehicles communicate continuously with one another, with the ability to link the sender of any one message to their previous messages - linkability. We observe that in academic literature and in industry, this linkability provision in not optimal. In protocols designed to give time-based linkability for nearby drivers, and unlinkability to prevent tracking, the continuity of communications is disrupted by unlinkable transitions; however for certain safety applications a continuous communication without this disruption in linkability is more fitting. In this light, we review the security requirements for safety messaging in Intelligent Transportation Systems (ITS). We propose a new distance-based approach to providing continuous linkability, and outline solutions for its provision